Imaji Musik dalam Metode Pelatihan Tari Jonet Sri Kuncoro terhadap Tuna Rungu - Joi El Java; Bondan Aji Manggala (FKIP, Universitas Palangka Raya, 2026)
This scientific article discusses the dance training method developed by Jonet Sri Kuncoro for the deaf (tunarungu), focusing on his experimental efforts to reinterpret the imagery of music and rhythm for their performance needs. The discovery of this method was triggered by Jonet's observation of persistent social dysfunction in the performing arts system, which applies standard conventional assessment criteria (Wirama, Wiraga, Wirasa) to deaf dancers, thus restricting their freedom of expression. The methodology employs qualitative research (fieldwork, personal approach) to understand the subjective experiences of the students. Theoretically, Jonet is positioned as a social change agent striving to overcome dysfunction in the social system of art (Talcott Parsons' Structural Functionalism) through adaptive strategies. The article concludes that Jonet's music-based dance learning method—rooted in a personal approach, the use of alternative musical codes (visual/mimicry/movement), and vibration technology—successfully redefines music as a tactile sensation. This method is effective in fostering self-confidence, enabling dance as an inclusive medium of expression, and simultaneously elevating the dignity and status of the deaf in society through performing arts.